Identification and antifungal susceptibility of a large collection of yeast strains isolated in Tunisian hospitals. (October 2013) - Eddouzi, Jamel; Lohberger, Andrea; Vogne, Christelle; Manai, Mohamed; Sanglard, Dominique
Abstract In this study, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) was used as a rapid method to identify yeasts isolated from patients in Tunisian hospitals. When identification could not be exstablished with this procedure, sequencing of the internal transcribed spacer with 5.8S ribosomal DNA (rDNA) (ITS1–5.8S–ITS2) and D1/D2 domain of large-subunit (LSU rDNA) were employed as a molecular approach for species differentiation. Candida albicans was the dominant species (43.37% of all cases), followed by C. glabrata (16.55%), C. parapsilosis (13.23%), C. tropicalis (11.34%), C. dubliniensis (4.96%), and other species more rarely encountered in human diseases such as C. krusei, C. metapsilosis, C. lusitaniae, C. kefyr, C. palmioleophila, C. guilliermondii, C. intermedia, C. orthopsilosis, and C. utilis. In addition, other yeast species were obtained including Saccharomyces cerevisiae, Debaryomyces hansenii (anamorph known as C. famata), Hanseniaspora opuntiae, Kodamaea ohmeri, Pichia caribbica (anamorph known as C. fermentati), Trichosporon spp. and finally a novel yeast species, C. tunisiensis. The in vitro antifungal activities of fluconazole and voriconazole were determined by the agar disk diffusion test and Etest, while the susceptibility to additional antifungal agents was determined with the Sensititre YeastOne system. Our results showed low incidence of azole resistance in C. albicans (0.54%), C. tropicalis (2.08%) and C. glabrata (4.28%). In addition, caspofungin was active against most isolates of the collection with the exception of two K. ohmeri isolates. This is the first report to describe caspofungin resistant isolates of this yeast.